IMPACT OF FAMILY AND NURSE SUPPORT ON SELF-CARE BEHAVIOR IN DIABETES MELLITUS PATIENTS - Gita angrini; Mikawati; Evi lusiana; Julianus ake; Hidayati ismail (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Diabetes mellitus is a metabolic disease characterized by increased blood glucose levels (hyperglycemia). This study aims to analyze the relationship between social support and nurse support with self-care behavior in diabetes mellitus patients in the working area of Samata Community Health Center, Gowa Regency. This research employs a quantitative approach with an analytical observational design using a cross-sectional study. The sample was selected using a non-probability sampling method with a purposive sampling approach, resulting in a total of 66 respondents. Data collection instruments included questionnaires for social support, nurse support, and the Summary of Diabetes Self-Care Activities (SDCA) for self-care behavior. The results showed that 89 percent of respondents received social support, 80 percent received nurse support, and 76% demonstrated self-care behavior. Statistical analysis using the Chi-square test, specifically the Continuity Correction test, yielded a p-value of 0.009 (p-value < α = 0.05). The findings indicate a significant relationship between social support and self-care behavior among diabetes mellitus patients in the working area of Samata Community Health Center, Gowa Regency. Additionally, nurse support was found to be significantly associated with self-care behavior, as nurses play a crucial role as educators by providing accurate information to diabetes mellitus patients. Future research is encouraged to explore other variables to expand the reference framework.